Pendampingan Penyusunan E-LKPD Berbantuan Whizer.Me dalam Meningkatkan Kemampuan Literasi Digital Guru di SDN Pasirhalang 1 Kaupaten Sukabumi - Gani, Resyi Abdul; Sundari, Fitri Siti; Rahayu, Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology in the industrial era 4.0 requires elementary school teachers to have digital literacy skills and create technology-based LKPD learning tools. However, many teachers still use conventional LKPD, so they do not support 21st century skills and an independent curriculum with a deep learning approach. This service activity aims to assist teachers of SDN Pasirhalang 1 Sukabumi in compiling LKPD assisted by Whizer.Me applications and training digital literacy skills. The method used is participatory action with the ADDIE model (analysis, design, development, implementation, evaluation). As a result, teachers' digital literacy competencies increased significantly: the average pre-test score of 58 increased to 82 in the post-test (an increase of 41%). The resulting interactive e-LKPD received an expert validation score of 87% (very valid) and product quality of 85% (good–very good), especially in the aspects of interactivity (88%) and material uniformity (86%). As many as 93% of teachers feel that this mentoring is very useful to improve skills.